2013
DOI: 10.1177/0021998313477896
|View full text |Cite
|
Sign up to set email alerts
|

Modelling manufacturing deformations in corner sections made of composite materials

Abstract: A three-step Finite Element model has been implemented to predict the spring-in of L-shaped parts. The material property development during the cure has been modelled as step changes during transitions between viscous, rubbery and glassy states of the resin. The tool-part interaction is modelled as a sliding interface with a constant sliding shear stress. The effect of various material and geometric variables on the deformation of L-Section parts are investigated by a parameter sensitivity analysis. The spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…The distribution of temperature and degree of cure throughout the thickness of part can be neglected due to its thin thickness. Previous studies reported by Ersoy et al found that the tool-part interaction had substantial effects on the residual stresses and distortions in composite structures [5,19,44,45,[56][57][58][59]. The part is assumed to be connected to the mould and no slip is allowed during curing in this investigation.…”
Section: Effects Of Thermal Dependence On the Spring-in Of Composite mentioning
confidence: 93%
See 1 more Smart Citation
“…The distribution of temperature and degree of cure throughout the thickness of part can be neglected due to its thin thickness. Previous studies reported by Ersoy et al found that the tool-part interaction had substantial effects on the residual stresses and distortions in composite structures [5,19,44,45,[56][57][58][59]. The part is assumed to be connected to the mould and no slip is allowed during curing in this investigation.…”
Section: Effects Of Thermal Dependence On the Spring-in Of Composite mentioning
confidence: 93%
“…the equilibrium stiffness is temperature-dependence. Moreover, some simplified constitutive laws, including the path dependence constitutive model, the two step or three step finite element model and pseudo-viscoelastic model, are developed and validated to be applicable to modelling the residual stresses and distortions of composite structures recently [10,11,[44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…A 3D three step model was developed to predict the distortions due to processing using the basic process model previously developed and implemented in ABAQUS by Ersoy et al 13 and Ç ınar et al 14 In this model, the mechanical properties were assumed to be constant within each of the viscous, rubbery and glassy material phases, and the mechanical properties of a single lamina were assumed to be transversely isotropic.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…It is difficult to measure the properties in this step, and there are no data in the literature related to the viscous behaviour. Following the previous parametric study of Ç ınar et al, 14 the shear modulus in this step is assumed to be reduced by a factor of 5. The material in this step is assumed to be linear elastic.…”
Section: Steps Of Analysismentioning
confidence: 99%
See 1 more Smart Citation